Reusable Extractant and Direct Catalytic Mediation of Water/Oil/Chlorodifluoromethane Nano-Emulsion in Natural Gas Condensate for Efficient Conversion of Chloride Impurities Into the Dicopper Chloride Trihydroxide Nanoparticles - Banan Khorshid, Zohre; Doroodmand, Mohammad Mahdi (Frontiers in Chemistry, 2022)
This research introduces an oil-in-water (O/W) nano-emulsion (oil-water-CHClF_2) as the reusable extractant phase using liquid-liquid extraction methodology for the removal efficiently of Cl- and Hg(0) (between 90 and ~100 %, deepening on the nature of the natural gas condensate, NGC) at a brief separation time (< 3.0 min). Achieved safety of the NGC using this nano-emulsion results in efficient reduction in the corrosion rate during testing iron-based fragments (vs. the untreated ones as controls) and increase in the NGC economic value. Another advantage of the synthesized nano-emulsion is its capability and catalytic mediating behavior to efficiently separate and synthesize highly pure dicopper chloride trihydroxide nanoparticles. The synthesized nanoparticles were characterized by different analytical methods such as Fourier transform-infrared spectrometry, X-ray diffraction, X-ray photoelectron spectrometry, and also direct visualization by some electron microscopies. Direct synthesis, fast synthetic time (< 3.0 min), high purity (> 99 %), and scalability are the main advantages of this synthetic method. This nanoparticle is not only safe, but also is efficiently applicable in different industries, especially as an echo-friendly agricultural pesticide for different plants and tress such as pistachio. Consequently, this method is accepted as direct, simple, low cost and scalable conversion of some upstream industries with the downstream ones. All these possibilities are attributed to the intermediate transport properties of the introduced O/W nano-emulsion. At this condition, this reagent plays role as a recycled motor for the NGC purification and conversion of these impurities into the safe and usable products. To the best of knowledge, this research is considered as the first report that shows application of this O/W medium for both chloride and mercury removal from the NGC and its direct use as top-element in the synthesis of echo-friendly nanoparticles. This system is applicable in some parts of the fuel and oil centers of the “Middle East”.